The Experimental Oxime K027—A Promising Protector From Organophosphate Pesticide Poisoning. A Review Comparing K027, K048, Pralidoxime, and Obidoxime - Lorke, Dietrich E.; Petroianu, Georg A. (Frontiers in Neuroscience, 2019)
Poisoning with organophosphorus compounds (OPCs) is a major problem worldwide. Standard therapy with atropine and established oxime-type enzyme reactivators (pralidoxime, obidoxime) is unsatisfactory. In search of more efficacious broad-spectrum oximes, new bispyridinium (K-) oximes have been synthesized, with K027 being among the most promising. This review summarizes pharmacokinetic characteristics of K027, its toxicity and in vivo efficacy to protect from OPC toxicity and compares this oxime with another experimental bisquaternary asymmetric pyridinium aldoxime (K048) and two established oximes (pralidoxime, obidoxime). After intramuscular (i.m.) injection, K027 reaches maximum plasma concentration within ∼30 min; only ∼2% enter the brain. Its intrinsic cholinesterase inhibitory activity is low, making it relatively non-toxic. In vitro reactivation potency is high for ethyl-paraoxon-, methyl-paraoxon-, dichlorvos-, diisopropylfluorophosphate (DFP)- and tabun-inhibited cholinesterase. When administered in vivo after exposure to the same OPCs, K027 is comparable or more efficacious than pralidoxime and obidoxime. When given as a pretreatment before exposure to ethyl-paraoxon, methyl-paraoxon, DFP, or azinphos-methyl, it is superior to the Food and Drug Administration-approved compound pyridostigmine and comparable to physostigmine, which because of its entry into the brain may cause unwanted behavioral effects. Because of its low toxicity, K027 can be given in high dosages, making it a very efficacious oxime not only for postexposure treatment but also for prophylactic administration, especially when brain penetration is undesirable.